Scalar Verb Classes Scalarity, Thematic Roles, and Arguments in the Estonian Aspectual Lexicon - Tamm, Anne (Biblioteca di Studi di Filologia Moderna, 2012)
This monograph discusses scalar verb classes. It tests theories of linguistic form and meaning, arguments and thematic roles, using Estonian data. The analyses help to understand the aspectual structure of Estonian. In Estonian, transitive verbs fall into aspectual classes based on the type of case-marking of objects and adjuncts. The book relates the morphosyntactic frames of verbs to properties typically associated with adjectives and nouns: scalarity and boundedness. Verbs are divided according to how their aspect is composed. Some verbs lexicalize a scale, which can be bounded either lexically or compositionally. Aspectual composition involves the unification of features. Compositionally derived structures differ according to which of the aspectually relevant dimensions are bounded.